DENGUE HAEMORRHAGIC FEVER IN PREGNANCY: MATERNAL AND PRENATAL OUTCOMES - Maulinda Putri (Medistra Medical Journal (MMJ), 2025)
Dengue infections are increasing worldwide with 20,000 deaths per year. Indonesia is also experiencing an increase in dengue cases, with 15,977 cases and 124 deaths by 2024. Laboratory confirmation of dengue infection is essential as the wide spectrum of clinical presentations, ranging from mild febrile illness to multiple severe syndromes, can make accurate diagnosis difficult. DENV infection causes pathological changes, including upregulation of proinflammatory cytokines such as interleukin 6, interleukin 8, and TNF-5, which can alter normal pregnancy physiology. Studies found that dengue fever during pregnancy triples the risk of maternal mortality and dengue infection during pregnancy is associated with a higher risk of fetal growth disorders to miscarriage. In pregnancy, the management of dengue should be through a multidisciplinary team approach.